KEMAMPUAN PESERTA DIDIK DALAM MEMBUAT MIND MAPPING PADA PEMBELAJARAN MATEMATIKA - ., Eminatri (Jurnal Edukasi dan Penelitian Matematika, 2023)
Taking notes are important activities that students need to do while following the mathematics learning process. The notes will be useful to them as relevant guidelines to help complete the task or prepare for the exam. However, many learners do not take notes in mathematics learning. This is due to their lack of awareness of the benefits of notes in learning. One of the tips that can be done to overcome this is to take notes with mind mapping techniques. Mind mapping is a way of recording creatively, effectively and not boringly because in making it students are facilitated to express their thoughts / abilities and imagination to use various newly learned words / terms, symbols / images, and colors, so that the ideas mapped will last a long time in their memory. This is different from ordinary notes that are only in the form of narratives. This research has facilitated class XI mipa students of SMAN 8 Padang to make notes with mind mapping techniques. As a result, the ability to make mathematical mind mapping for students is in the sufficient category.  Keywords– Mind Mapping, Mathematics Learning.